Change in temperature extremes and its correlation with mean temperature in mainland China from 1960 to 2015. (23rd December 2016) - Fang, Shibo; Qi, Yue; Yu, Weiguo; Liang, Hanyue; Han, Guojun; Li, Qingxiang; Shen, Shuanghe; Zhou, Guangsheng; Shi, Guangxun
ABSTRACT: Changes in temperature extremes can be linked to mean temperature changes and variability. This study aims to quantify observed trends in mean and extreme temperature values and to analyse the relationship between mean and extreme temperatures in mainland China, based on daily data from 1960 to 2015. This is the first analysis undertaken of the relationship between mean and extreme temperatures in mainland China. Based on the 95th and 99th percentiles of daily T max and the 5th and 1st percentiles of daily T min, warm days (TX95p), hot days (TX99p), cold nights (TN05p), and very cold nights (TN01p) were defined. The results showed the following: (1) large increasing tendencies of TX95p and TX99p nearly all occurred in locations where mean temperature had substantially increased, and large decreasing tendencies of TN05p were more probably at locations of warming in mainland China; (2) the rise of mean temperature significantly increased the frequency of TX95p and TX99p, and decreased the frequency of TN05p, which indicates a simple shift of the entire distribution towards a warmer climate and greater potential risk of heat waves in the future. The likelihood of occurrence of TX95p and TX99p increased by about 3 and 1 day, respectively, and the occurrence of TN05p was reduced by about 4 days with a mean temperature increase of 1 °C, but the occurrence of TN01p was hardly affected, indicating increased variability of T min temperatures; and (3) the mean and extreme temperatures increased with the urbanization rate in China, and advanced phenologies and unaffected frequency of very cold nights (TN01p) could pose more potential risk of frost and freeze injury to crops in China in the future.